2022
DOI: 10.1186/s13059-022-02736-5
|View full text |Cite
|
Sign up to set email alerts
|

Target residence of Cas9-sgRNA influences DNA double-strand break repair pathway choices in CRISPR/Cas9 genome editing

Abstract: Background Due to post-cleavage residence of the Cas9-sgRNA complex at its target, Cas9-induced DNA double-strand breaks (DSBs) have to be exposed to engage DSB repair pathways. Target interaction of Cas9-sgRNA determines its target binding affinity and modulates its post-cleavage target residence duration and exposure of Cas9-induced DSBs. This exposure, via different mechanisms, may initiate variable DNA damage responses, influencing DSB repair pathway choices and contributing to mutational h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 74 publications
3
52
0
Order By: Relevance
“…Studies of DSBs induced by CRISPR/Cas9 in endogenous chromatin have primarily focused on mutagenic repair, revealing many aspects affecting editing outcome and repair-pathway choice 41,42 . In addition, kinetic studies have provided insight into the dynamics of the process of induction and error-prone repair [43][44][45][46] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of DSBs induced by CRISPR/Cas9 in endogenous chromatin have primarily focused on mutagenic repair, revealing many aspects affecting editing outcome and repair-pathway choice 41,42 . In addition, kinetic studies have provided insight into the dynamics of the process of induction and error-prone repair [43][44][45][46] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of DSBs induced by CRISPR/Cas9 in endogenous chromatin have primarily focused on mutagenic repair, revealing many aspects affecting editing outcome and repair-pathway choice 41,42 . In addition, kinetic studies have provided insight into the dynamics of the process of induction and error-prone repair 4346 . However, as a result of the inability to directly observe scar-less re-ligation, measuring the degree of precise repair, particularly by the end-joining pathways, remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Fusion of HDR facilitators to the widely used Cas nuclease Streptococcus pyogenes Cas9 ( Sp Cas9) and arresting the cell cycle at the S/G2 phase by chemicals have improved HDR-mediated CRISPR genome editing ( 3 , 9 , 12–18 ). Chemical inhibition or genetic inactivation of c-NHEJ, the most dominant competing pathway against HDR, could channel DSBs that are supposedly repaired by c-NHEJ to HDR, thereby increasing the efficiency of HDR in repair of Cas nuclease-induced DSBs ( 3 , 8 , 9 ). Indeed, inhibition of c-NHEJ is often used to promote HDR-mediated genome editing ( 3 , 9 , 19–22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, inhibition of c-NHEJ is often used to promote HDR-mediated genome editing ( 3 , 9 , 19–22 ). However, due to global inhibition of c-NHEJ, our recent study demonstrated that this approach unavoidably exacerbates off-target effect ( 8 ). We reason this off-target problem could be solved by local inhibition of c-NHEJ; but such a strategy has yet to be developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation